Marine life and fisheries around offshore oil and gas structures in southeastern Australia and possible consequences for decommissioning - Sih, Tiffany L.; Cure, Katherine; Yilmaz, I. Noyan; McLean, Dianne; Macreadie, Peter I. (Frontiers in Marine Science, 2022)
The Gippsland Basin is the location of Australia’s oldest offshore oil and gas (O&G) structures, with hydrocarbon production beginning in the 1960s. The Bass Strait flows over this area with fisheries providing seafood for the major population centers of Melbourne, Sydney and beyond. Since Australia’s maritime legislation restricts activities to outside of 500 meters from O&G structures as a security exclusion zone, these O&G structures may serve as de facto marine protected areas that may have spillover effects to local fisheries. Therefore, it is critical to understand the habitat value of O&G infrastructure to marine life in the Bass Strait and whether decommissioning of these structures affect local marine ecosystems and fisheries. We analyzed industry-collected remotely operated vehicle (ROV) imagery from 2008-2018 and compared this data with reported catch data from fishing vessels operating in this region collected by the Australian Fisheries Management Authority (AFMA) from 2008-2018. We assessed species richness and relative abundance on two platforms and two pipelines and compared the species composition with retained catch reported by commercial fishers operating in Commonwealth fisheries. We found diverse communities of fishes and invertebrates around O&G structures, with a different subset of species inhabiting pipelines than platforms. We found little overlap between the species that were targeted by commercial fishers and those found around O&G structures (10% overlap), however, species composition data from fisheries often groups species making the data coarse and under-representative of true species diversity. Fishery-independent data from ROV imagery or other methods greatly augments our understanding of deepwater marine communities, including those around O&G structures. Combining data sources provides a holistic look at these novel ecosystems and provides better insight into future decommissioning scenarios.